Experiences of the public on the services in emergency department: a qualitative study - Aung, Khin Thandar; Saiful Bahri, Fatin Izzati (Kulliyyah of Nursing, International Islamic University Malaysia, 2018)
Objective: The purpose of this study was to explore the experiences of the public on the services provided in the Emergency Department (ED) of Hospital Tengku Ampuan Afzan (HTAA) . Methods: An exploratory, descriptive design was used to understand public experiences on the services in the ED. Ten respondents who fit the inclusion criteria were selected using purposive sampling method during their visit to the ED. They were interviewed for 30 to 45 minutes and were audio-recorded with the permission of the participants. The general meaning and the tone conveyed by the respondents were determined through coding, descriptions, and the themes that emerged. Results: Four major themes emerged from the study including waiting time, ED staff, information regarding the ED, and expectation on the ED services. Conclusion: As a result, there is a need to improve the practices in the ED and a need for an awareness program on the real functions and services of the ED.